Factors Influencing Customer Loyalty at Bank Rakyat Indonesia Cash Office Panti Waluyo Hospital Surakarta: A Study on the BRImo Application - Jaguar Dwi Pratama Christiawan; Rosita Mei Damayanti (Vocational School, Universitas Sebelas Maret (UNS), Indonesia, 2024)
The lack of popularity of the BRImo application at the BRI Cash Office of Panti Waluyo Hospital in Surakarta serves as the background of this research. The aim of this research is to identify the factors that influence customer loyalty among BRImo users. The independent variables investigated in this research are system quality, user interface design, service quality, and security guarantees, while the dependent variable is user-customer loyalty. This research employed a quantitative approach, collecting data through a closed questionnaire utilizing a Likert scale. The sample consisted of 100 customers using the BRImo application at the PT Bank Rakyat Indonesia Cash Office in Pati Waluyo Hospital Surakarta. Data analysis was conducted using the SPSS software version 23.0. The results indicate that, when considered together, system quality, user interface design, service quality, and security guarantees have a significant effect on the customer loyalty of BRImo users. However, when analyzed individually, system quality and service quality do not significantly affect customer loyalty, whereas user interface design and security guarantees do have a significant impact on loyalty among BRImo users.